(untitled) (Applied Biological Research, 2023)
An experiment was conducted to evaluate the impact of chlorantraniliprole and fipronil on the bacterial population of gut of Eisenia fetida and its vermicast. Thirty adult earthworms were exposed to chlorantraniliproleand fipronil-treated cow dung in 30 L capacity tub. Enumeration was done by spread plate technique and the bacteria were identified on the basis of morpho-biochemical characteristics. Studies revealed that E. fetida survived even after the exposure to high concentration of chlorantraniliprole and fipronil, perhaps due to the presence of tolerant bacteria in the earthworm’s gut. The chlorantraniliprole and fipronil largely affected the bacterial population in earthworm’s gut and its vermicast. Chlorantraniliprole proved more harmful than fipronil. Maximum reduction in total viable tolerant bacterial colonies in earthworm gut and vermicast was 2.42 and 2.95%, respectively, when exposed to the mixed concentration of chlorantra-niliprole and fipronil (5.00 and 8.34 mg kg-1, respectively). Overall, the vermicast had more tolerant bacterial colonies than the gut of E. fetida.